Percutaneous Coronary Intervention in Acute Coronary Syndrome with Mild-to-Moderate Thrombocytopenia - Ye, Yicong; Hao, Yongchen; Zhao, Xiliang; Liu, Jun; Yang, Na; Smith, Sidney C., Jr; Huo, Yong; Fonarow, Gregg C.; Ge, Junbo; Morgan, Louise; Sun, Zhaoqing; Hu, Danqing; Yang, Yiqian; Ma, Chang-Sheng; Zhao, Dong; Han, Yaling; Liu, Jing; Zeng, Yong (Thrombosis and Haemostasis, 2024)
Background Baseline thrombocytopenia is commonly observed in patients with acute coronary syndrome (ACS) requiring percutaneous coronary intervention (PCI).Aim The purpose of this analysis was to investigate safety and effectiveness of PCI in ACS patients with baseline mild-to-moderate thrombocytopenia.Methods The data were collected from the Improving Care for Cardiovascular Disease in China–Acute Coronary Syndrome project. A total of 50,009 ACS patients were recruited between July 2017 and December 2019. Among them, there were 6,413 patients with mild-to-moderate thrombocytopenia, defined as a platelet count of ≥50 × 109/L and <150 × 109/L on admission. The primary outcome was in-hospital net adverse clinical events (NACE), consisting of major adverse cardiac events (MACE) and major bleeding events. The associations between PCI and in-hospital outcomes were analyzed by inverse probability treatment weighting (IPTW) method.Results PCI was performed in 4,023 of 6,413 patients (62.7%). The IPTW analysis showed that PCI was significantly associated with a reduced risk of in-hospital MACE (odd ratio [OR]: 0.45; 95% confidence interval [CI]: 0.31–0.67; p < 0.01) and NACE (OR: 0.59; 95% CI: 0.42–0.83; p < 0.01). PCI was also associated with an increased risk of any bleeding (OR: 1.56; 95% CI: 1.09–2.22; p = 0.01) and minor bleeding (OR: 1.52; 95% CI: 1.00–2.30; p = 0.05), but not major bleeding (OR: 1.51; 95% CI: 0.76–2.98; p = 0.24).Conclusion Compared with medical therapy alone, PCI is associated with better in-hospital outcomes in ACS patients with mild-to-moderate thrombocytopenia. Further studies with long-term prognosis are needed.
Keywords: thrombocytopenia; acute coronary syndrome; percutaneous coronary intervention; platelet